Vertical CNT-Si Photodiode Array - Ahnood, Arman (2013)
A photodiode consisting of nanopillars of thin-film silicon p-i-n on an array of vertically aligned carbon nanotubes (CNTs) with a noncontinuous cathode electrode is demonstrated. The structure exploits the intrinsic enhancement of the CNTs' electric field, which leads to reduction in the photodiode's operating voltage and response time and enhancement of optical coupling due to better light trapping, as compared with the conventional planar photodiode. These improvements translate to higher resolution and higher frame rate flat-panel imaging systems for a broad range of applications, including computed tomography and particle detection.